2015
DOI: 10.1007/s00068-015-0499-7
|View full text |Cite
|
Sign up to set email alerts
|

13-Year experience in external fixation of the pelvis: complications, reduction and removal

Abstract: While previous data suggest high complication rates in definitive anterior pelvic external fixation, we present the largest cohort of patients receiving anterior pelvic external fixation and sacroiliac screws, demonstrating a low complication rate while maintaining reduction of the pelvic ring. In addition, we found that these devices could be reliably removed in a clinic setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…EF is an osteosynthesis technique characterized by its minimal invasivity, relative simplicity of application, and lower cost compared to internal osteosynthesis implants ( 26 , 27 ). To the best of our knowledge, no previous studies have described the use of EF for sacral fractures in the veterinary literature.…”
Section: Discussionmentioning
confidence: 99%
“…EF is an osteosynthesis technique characterized by its minimal invasivity, relative simplicity of application, and lower cost compared to internal osteosynthesis implants ( 26 , 27 ). To the best of our knowledge, no previous studies have described the use of EF for sacral fractures in the veterinary literature.…”
Section: Discussionmentioning
confidence: 99%
“…17 Pin removal can often be accomplished in the clinic setting, although removal in the operating room is still preferred at many centers. 18…”
Section: Supraacetabular Pinsmentioning
confidence: 99%
“…20 More recent studies on the use of anterior external fixation supplemented by iliosacral screws reported much lower complication rates. Mitchell et al 18 reported the maintenance of reduction in 86.5% of patients after frame removal with an average change in symphyseal diastasis of only 2.8 mm. Tosounidis et al 17 also reported satisfactory functional outcomes in 74.5% despite a malunion rate of 30.5%.…”
Section: Complications/outcomesmentioning
confidence: 99%
“…2023, 10, 656 2 of 16 In human medicine, the acute management of pelvic fractures by external fixation (EF) is commonly performed to avoid displacement of the fracture site, bleeding, neurovascular damage and/or post-traumatic pain [7]. Additionally, EF is a valuable technique for definitive stabilization due to its low rate of complications and ease of application [7][8][9].…”
Section: Introductionmentioning
confidence: 99%